Community empowerments strategy for economic opportunities in Selayar Islands Regency, South Sulawesi - Ilham Junaid (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Indonesia is an archipelagic state with considerable potential as tourism destinations, yet that potential has not been fully maximized. This paper aims to examine the opportunity and potential of Gusung Island as tourism resources and propose possible strategies to manage the tourism resources of Gusung Island, Selayar Islands Regency. The research was conducted in July and August 2019 on Gusung Island, Selayar Islands Regency, South Sulawesi Province by applying qualitative research methods. Methods of data collection are through in-depth interviews with the fishing community and their families, direct observation or observation in Gusung Island, and focused discussions held in Benteng City, Selayar Islands Regency. The research reveals that marine tourism and local community activities have a considerable potential to support Gusung Island as a tourism destination. Strategies for community empowerment include educating and facilitating community for hospitality skills, creating tourism packages by involving the tourism industry and the local community, strengthening the working group’s role in managing the tourism resources of Gusung Island. Sustainable tourism may be booming if the local community organizations play a pivotal role in facilitating the local community to preserve the environment.